A membrane-bound ankyrin repeat protein confers race-specific leaf rust disease resistance in wheat - Kolodziej, Markus C.; Singla, Jyoti; Sánchez-Martín, Javier; Zbinden, Helen; Šimková, Hana; Karafiátová, Miroslava; Doležel, Jaroslav; Gronnier, Julien; Poretti, Manuel; Glauser, Gaétan; Zhu, Wangsheng; Köster, Philipp; et al. (Nature communications, 2021)
Plasma membrane-associated and intracellular proteins and protein complexes play a pivotal role in pathogen recognition and disease resistance signaling in plants and animals. The two predominant protein families perceiving plant pathogens are receptor-like kinases and nucleotide binding-leucine-rich repeat receptors (NLR), which often confer race-specific resistance. Leaf rust is one of the most prevalent and most devastating wheat diseases. Here, we clone the race-specific leaf rust resistance gene Lr14a from hexaploid wheat. The cloning of Lr14a is aided by the recently published genome assembly of Arina LrFor , an Lr14a -containing wheat line. Lr14a encodes a membrane-localized protein containing twelve ankyrin (ANK) repeats and structural similarities to Ca 2+ -permeable non-selective cation channels. Transcriptome analyses reveal an induction of genes associated with calcium ion binding in the presence of Lr14a . Haplotype analyses indicate that Lr14a- containing chromosome segments were introgressed multiple times into the bread wheat gene pool, but we find no variation in the Lr14a coding sequence itself. Our work demonstrates the involvement of an ANK-transmembrane (TM)-like type of gene family in race-specific disease resistance in wheat. This forms the basis to explore ANK-TM-like genes in disease resistance breeding. Winter wheat cultivar Forno harbors a race-specific leaf rust resistance locus Lr14a , but the causative gene is unknown. Here, the authors show that Lr14a encodes a membrane-localized protein containing ankyrin repeats and Lr14a -containing segments have been introgressed into the bread wheat gene pool multiple times.